Improving Early Stakeholder Engagement Process: An Empirical Study of Rapid Transit Railway of Malaysian Project - Baharuddin, Har Einur Azrin; Mokhtar Azizi, Nurul Sakina; Piri, Imelda (International Journal of Sustainable Construction Engineering and Technology, 2022)
Stakeholders in infrastructure projects should be steadily engaged starting from the earliest stage of the project i.e pre construction, until completion of the project. Stakeholder which directly and indirectly engaged in a large infrastructure projects, has different desires, interests, rights, and also can be voiceful. The main purpose of engaging of with the stakeholder is to promote fairness and trustworthy both to the external and internal stakeholder because as individuals and groups who are excluded from the decision-making processes are unlikely not to have their needs and preferences reflected in the outcome. The purpose of the paper aims to focus on improvement on the process of stakeholder engagement in Malaysian railway case study focusing on planning stage. This paper applies a qualitative research methodology based on semi-structured interviews and observation from a single case study of a mass rapid transit railway project in Malaysia. Empirical study from the case study will lead to establish lesson learned that could improve the stakeholder engagement scheme in infrastructure projects. The findings explained the sequence by showing the improvement of stakeholder engagement processes that need to be done during the pre-construction process. The suitable engagement process involves internal preparation and alignment, consulting, monitoring and planning. Albeit engagement process is a difficult to manage, it requires courage and humility when dealing with the public and community.